Scalable multifunctional MOFs-textiles via diazonium chemistry - Li, Wulong (2024)
Cellulose fiber-based textiles are ubiquitous in daily life for their processability, biodegradability, and outstanding flexibility. Integrating cellulose textiles with functional coating materials can unlock their potential functionalities to engage diverse applications. Metal-organic frameworks (MOFs) are ideal candidate materials for such integration, thanks to their unique merits, such as large specific surface area, tunable pore size, and species diversity. However, achieving scalable fabrication of MOFs-textiles with high mechanical durability remains challenging. Here, we report a facile and scalable strategy for direct MOF growth on cotton fibers grafted via the diazonium chemistry. The as-prepared ZIF-67-Cotton textile (ZIF-67-CT) exhibits excellent ultraviolet (UV) resistance and organic contamination degradation via the peroxymonosulfate activation. The ZIF-67-CT is also used to encapsulate essential oils such as carvacrol to enable antibacterial activity against E. coli and S. aureus. Additionally, by directly tethering a hydrophobic molecular layer onto the MOF-coated surface, superhydrophobic ZIF-67-CT is achieved with excellent self-cleaning, antifouling, and oil-water separation performances. More importantly, the reported strategy is generic and applicable to other MOFs and cellulose fiber-based materials, and various large-scale multi-functional MOFs-textiles can be successfully manufactured, resulting in vast applications in wastewater purification, fragrance industry, and outdoor gears.